Resistive DC fault current limiter. Issue 13 (19th December 2017) - Sujuan, Xie; Yufeng, Qiu; Tianshu, Bi
Abstract : The DC fault current of bipolar short‐circuit fault rises rapidly due to the low damping performance of the modular multilevel converter‐high‐voltage DC (MMC‐HVDC) system. It is of great engineering significance to study the DC fault current limiter (FCL) in HVDC systems for suppressing the DC fault current, resulting in making the DC circuit breaker broken the fault line easily. Here, the influences of the DC FCL on the current suppression of DC short circuit fault are analysed in detail according to the characteristics of DC short‐circuit fault in MMC‐HVDC system. A new type of resistive DC fault current‐limiting device which consists of a control module and a damping module is proposed here. This device can increase the damping performance of the DC fault current loop and effectively limit the rising rate of DC fault current. By doing so, it is helpful for the DC circuit breaker to disconnect the DC fault line more easily and prevent the converters locking due to over‐current. Finally, the effectiveness of the DC FCL is validated by the PSCAD/EMTDC simulation model.